TIDAL REGIMS OF ARAFURA AND TIMOR SEA - Pranowo, Widodo S.; Wirasantosa, Sugiarta (Marine Research in Indonesia, 2011)
Tidal range in the Arafura and Teimor Sea region is estimated from the actual field records collected by five tidal stations during March 2011. These stations include Rote and Saumlaki tidal stations of Badan Koordinasi Survei dan Pemetaan Nasional (Bakosurtanal) Indonesia, and Broome, Darwin and Groote Eylandt tidal stations of Australia Bureau of Meteorology (BoM). In addition to data from these stations, datasets of sea surface height obtained from Topex/Poseidon altimetry at seven (7) virtual stations were used. Generally, the results of this study are in agreement with that of Wyrtki (1961). However, by utilizing spectral analysis and form factor, this study shows difference in terms of tidal types from that of Wyrtkis, particularly at Karumba and Groote Eylandt stations.